MENINGKATKAN PENGETAHUAN JUS BUAH BUAHAN YANG ADA DISEKITAR LINGKUNGAN TEMPAT TINGGAL MASYARAKATUNTUK MENURUNKAN HIPERTENSI DI PERKUMPULANYASINANKELUARGA USWATUN KHASANAH DI DUSUNBARAHAN DESA TARUB KECAMATANTAWANGHARJO KABUPATENGROBOGAN - purhadi (LPPM AN Nuur, 2026)
Background: Hypertension is a condition where blood pressure is above normal, at ≥140/90 mmHg. It is often referred to as a silent killer because it often has no symptoms but can lead to serious complications such as stroke, heart disease, and kidney failure. Non-pharmacological efforts to lower blood pressure include consuming potassium-rich fruit juices (starfruit, tomato, watermelon, orange, and dragon fruit). This juice lowers blood pressure by increasing sodium excretion through urine, thereby helping maintain fluid balance and blood pressure. Objective: Participants will increase their knowledge about fruits and the process of making fruit juices to reduce hypertension. Method: This activity uses a scientific lecture method and practical fruit juice making sessions. Results: The evaluation was conducted by asking participants questions about the theory of various fruits that can lower hypertension and the process of making fruit juices. 100% of the women in attendance were able to answer questions regarding the theory and practice of making fruit juices. Conclusion: The knowledge outreach and demonstration of making fruit juices (starfruit, tomato, watermelon, orange, and dragon fruit) were very effective in increasing participants' knowledge because they were accompanied by demonstrations on how to properly make fruit juices.